Regression from Pre-diabetes to Normal Glucose Regulation is Associated with Long-term Reduction in Diabetes Risk: Results from the Diabetes Prevention Program Outcomes Study - Perreault, Leigh (2012)
BACKGROUND: Our objective was to quantify and predict diabetes risk reduction during the Diabetes Prevention Program Outcomes Study (DPPOS) among those who returned to normal glucose regulation (NGR) at least once during DPP compared to those who were consistently considered to have pre-diabetes. METHODS: Diabetes cumulative incidence in DPPOS was calculated for subjects with NGR or pre-diabetes status during DPP with and without stratification by prior randomized treatment group. Cox proportional hazards modeling and generalized linear mixed models were used to quantify the impact of previous (DPP) glycemic status on risk of later (DPPOS) diabetes and NGR status, respectively, per standard deviation in change. Included in this analysis are 1990 participants of DPPOS (who had been randomized during DPP: N=736 in intensive lifestyle (ILS), N=647 to metformin (MET), and N=607 to placebo (PLB)). FINDINGS: Diabetes risk during DPPOS was 56% lower in NGR vs. pre-diabetes (HR=0.44, 95% CI 0.37-0.55, p<0.0001) and was unaffected by prior group assignment (interaction test for NGR*ILS, p=0.1722; NGR*MET, p=0.3304). Many, but not all, of the variables that increased diabetes risk were inversely associated with the chance of reaching NGR status in DPPOS. Specifically, having had prior NGR (OR=3.18, 95% CI 2.71-3.72, p<0.0001), higher β-cell function (OR=1.28; 95% CI 1.18-1.39, p<0.0001) and insulin sensitivity (OR=1.16, 95% CI 1.08-1.25, p<0.0001) were associated with NGR in DPPOS, whereas the opposite was true for predicting diabetes (HR=0.80, 95% CI 0.71-0.89; HR=0.83, 95% CI 0.74-0.94, respectively, p<0.0001 for both). Surprisingly, among subjects who failed to return to NGR in DPP, those randomized to ILS had a higher diabetes risk (HR=1.31, 95% CI 1.03-1.68, p=0.0304) and lower chance of NGR (OR=0.59, 95% CI 0.42-0.82, p=0.0014) vs. placebo in DPPOS. INTERPRETATION: We conclude that pre-diabetes represents a high-risk state for diabetes, especially among those who remain so despite ILS. Reversion to NGR, even if transient, is associated with a significantly lower risk of future diabetes independent of prior treatment group.